Biogas from a Mixture of Banana Stalks and Chicken Manure: Biogas dari Campuran Batang Pisang dan Kotoran Ayam - Dwiguna Bestari; Vivi Indriani; Monasdir (Jurnal Peternakan Integratif, 2026)
The laying hen farming business produces manure that can pollute the environment if not handled properly. Processing laying chicken manure needs to be done to reduce negative impacts on the environment. Biogas technology uses raw materials derived from livestock manure to create a renewable alternative fuel source. The research's goal is to assess the biogas potential of a combination of laying chicken manure and banana stems. This research used a completely randomised design (CRD) with 3 treatments, namely the control (K100B0: 100% chicken manure), treatment 1 (K70B30: 70% chicken manure and 30% banana stems), and treatment 2 (K50B50: 50% chicken manure and banana stems) which are stored in a 30 litre digester for 35 days. The parameters observed in this research were pH, total solids (TS), volatile solids (VS), flame test, and gas volume. The initial and final TS and VS in treatments 1 and 3 indicated that biogas production was higher than the control. Treatments 1 and 2 produced a longer, blue flame with a higher methane content than the control, with T1 of 177.5 and P2 of 665.0 mL. The results of this research indicate the high potential for using laying chicken manure and banana stems as materials for making biogas.